Video Analysis of 26 Cases of Second ACL Injury Events in Collegiate and Professional Athletes - Manuela Vargas; Grace K Chaney; María C. Mejía Jaramillo; Paige Cummings; April McPherson; Nathaniel A. Bates (International Journal of Sports Physical Therapy)
# Background